Bunium allioides(Apiaceae), a New Species from Turkey - Kljuykov, Evgeniy V.; Degtjareva, Galina V.; Bani̇, Bariş; Pimenov, Michael G.; Adiguzel, Nezaket (Finnish Zoological and Botanical Publishing Board, 2012)
Bunium allioides B. Bani, Pimenov & Adiguzel sp. nova (Apiaceae), is described and illustrated from southern (Mediterranean) Turkey. The taxonomic affinities of the new species were determined by analysing morphological data and a molecular phylogenetic study of nrDNA ITS sequences. Bunium allioides belongs to the section Elegantia, and is related to B. paucifolium and B. elegans.